Intracranial volume–pressure relationships during experimental brain compression in primates: 1. Pressure responses to changes in ventricular volume - Leech, Peter (1974)
Intermittent additions of 0·05 ml saline were made into the lateral ventricle of anaesthetized, ventilated baboons at regular intervals during continuous inflation of a supratentorial extradural balloon. Close correlation was observed both between the increase in ventricular fluid pressure (VFP) immediately after the injection and the volume in the balloon (P < 0·001); and between the increase in ventricular pressure and the pressure immediately before the injection (P < 0·001). This change in ventricular fluid pressure, which is termed the volume–pressure response (VPR), helps to delineate the stage reached on the intracranial volume–pressure curve, and is therefore a measure of the capacity of the intracranial contents to compensate for the volume changes produced by an expanding intracranial lesion. The VPR is currently being used in patients and the clinical implications of confirming its validity experimentally are therefore discussed.